A wicked snow eaudiobook - Olsen, Gregg (Tantor Media, 2020)
Hannah Griffin was a girl when tragedy struck. She still remembers the flames reflected against the newly fallen snow and the bodies the police dug up—one of them her mother's. The killer was never found . . . Twenty years later Hannah is a talented CSI investigating a case of child abuse when the past comes hurtling back. A killer with unfinished business is on the hunt. And an anonymous message turns Hannah's blood cold: Your Mom called . . . Contains mature themes.